Quantitative and Qualitative Aspects of Influence of the Investments on Economic Growth - Oleinik, Elena; Zakharova, Alena (International Journal of Economics and Financial Issues, 2016)
The problem of ensuring a steady economic growth is critical for successful development of the economy, and inflow of investments is one of the most important indicators of the economic advance. The modern conditions of development of economic systems have necessitated more precise directions of investment process for the economic growth to accelerate. With regard to this, the relevance of a comprehensive analysis and evaluation of connection between the investment activity and the economic growth increases. This paper presents a comparative analysis of notions and approaches to evaluation of the role of investments in achieving a steady economic advance. In order to evaluate the quantitative and qualitative factors of the investment activity influencing the buoyancy of economy, index methods and correlation and regression analysis ones were used. The authors suggest applying the indices of "input" and "return" of the investments. The quality of investments is characterized by directions of the investment activity. The quantitative aspect is characterized by a "quick" and "deferred" return of investments. The dependence of economic growth on the indices elaborated was studied on the basis of indices of the economic development of Russia. The suggested approach of quantitative and qualitative evaluation of investment activity and the elaborated indices can be used as an auxiliary tool for forming the investment policy both at the level of the country and at that of regions. Keywords: economic growth, gross domestic product, investments, investment activity. JEL Classifications: Ð¡54; Ð¡01; Ð•22